2006
DOI: 10.1016/j.pmcj.2006.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysing fundamental properties of marker-based vision system designs

Abstract: This paper investigates fundamental properties of Marker-based Vision (MBV) systems. We present a theoretical analysis of the performance of basic tag designs which is extended through simulation to investigate the effects of different processing algorithms. Real-world data are processed and related to the simulated results. Image processing is performed using Cantag, an open source software toolkit for building Marker-based Vision (MBV) systems that can identify and accurately locate printed markers in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Different types of markers can be used for reality augmentation, where according to [1] and [13] the most common markers are: bars (e.g., QR, DataMatrix, PDF-417), circles (e.g., CircleInner, CircleSplit, CircleOuter, SpotCode), squares (ID markers, binary), and images (e.g., StudierStube). In [1] it is shown that square marker with a thick border is the most accurate for marker-based systems.…”
Section: A Markers and Their Identitymentioning
confidence: 99%
See 3 more Smart Citations
“…Different types of markers can be used for reality augmentation, where according to [1] and [13] the most common markers are: bars (e.g., QR, DataMatrix, PDF-417), circles (e.g., CircleInner, CircleSplit, CircleOuter, SpotCode), squares (ID markers, binary), and images (e.g., StudierStube). In [1] it is shown that square marker with a thick border is the most accurate for marker-based systems.…”
Section: A Markers and Their Identitymentioning
confidence: 99%
“…To add more, markers are important AR tool because of their high degree of accuracy to capture [1], [4], [13]. The system should also be able to calculate the position of the camera using the detected marker.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Circular markers such as TRIP [15] and InterSense's markers [19] also contain an identification tag, but the pose must be estimated using the shape of the projected circle, or with the help of multiple markers. According to Rice et al [20] square markers can contain more data, but the pose can be calculated more accurately with the help of circular markers. Another more recent form of fiducial markers are marker fields [23].…”
Section: Related Workmentioning
confidence: 99%